Caspase-9 inhibitor Z-LEHD-FMK enhances the yield of in vitro produced buffalo (Bubalus bubalis) pre-implantation embryos and alters cellular stress response. (February 2016) - Mullani, N.; Singh, M.K.; Sharma, A.; Rameshbabu, K.; Manik, R.S.; Palta, P.; Singla, S.K.; Chauhan, M.S.
Abstract: The present investigation was done to study the effect of caspase-9 inhibitor Z-LEHD-FMK, on in vitro produced buffalo embryos. Z-LEHD-FMK is a cell-permeable, competitive and irreversible inhibitor of enzyme caspase-9, which helps in cell survival. Buffalo ovaries were collected from slaughterhouse and the oocytes were subjected to in vitro maturation (IVM), in vitro fertilization (IVF) and in vitro culture (IVC). The culture medium was supplemented with Z-LEHD-FMK at different concentrations i.e. 0 μM (control), 10 μM, 20 μM, 30 μM and 50 μM during IVM and IVC respectively. After day-2 post-insemination, the cleavage rate was significantly higher (74.20 ± 5.87% at P < 0.05) in the group treated with 20 μM of Z-LEHD-FMK than at any other concentration. Same trend was observed in the blastocyst production rate which was higher at 20 μM (27.42 ± 2.94% at P < 0.05). The blastocysts obtained at day-8 of the culture at different concentrations were subjected to TUNEL assay, to determine the level of apoptosis during the culture medium supplied with 20 μM Z-LEHD-FMK which showed apoptotic index significantly lower (1.88 ± 0.87 at P < 0.05). There was a non-significant increase in total cell number in all Z-LEHD-FMK treated blastocysts. The quantitative gene expression of CHOP and HSP10 genes showed significant increase (P < 0.05) in the group treated with 50 μM Z-LEHD-FMK, while, HSP40 showed significant increase (P < 0.05) at 30 μM and 50 μM Z-LEHD-FMK concentrations. From the afore mentioned results we conclude that, Z-LEHD-FMK at 20 μM increased the cleavage and blastocyst rate of buffalo pre-implantation embryos also affecting the rate of apoptosis and cellular stress at various concentrations. Highlights: Z-LEHD-FMK at lower concentrations increased the embryo production. Z-LEHD-FMK reduced cellular stress and apoptosis in embryonic cells. Z-LEHD-FMK affects the mitochondrial stress and apoptosis related genes in embryos.